Mineralogy of air-pollution-control residues from a secondary lead smelter: environmental implications - Ettler, Vojtech; Johan, Zdenek; Baronnet, Alain; Jankovsky, Filip; Gilles, Christian; Mihaljevic, Martin; Sebek, Ondrej; Strnad, Ladislav; Bezdicka, Petr (Environmental science & technology, 2005)
The mineralogy and solubility of air-pollution-control (APC) residues from a secondary lead (Pb) smelter have been studied on samples from the Príbram smelter, Czech Republic, recycling car batteries, with the emphasis on their potential environmental effect. The presence of dominant anglesite (PbSO4) and laurionite (Pb(OH)Cl) was observed in a sintered residue from after-burning chambers (800-1000 degrees C). In contrast, low-temperature Pb-bearing phases, such as KCl x 2PbCl2 and caracolite (Na3Pb2(SO4)3Cl), were detected in the major APC residue from bag-type fabric filters. Metallic elements, zinc (Zn), cadmium (Cd), and tin (Sn) were found homogeneously distributed within this residue. The formation of anglesite, cotunnite (PbCl2), (Zn,Cd)2SnO4, and (Sb,As)2O3 was observed during the sintering of this APC residue at 500 degrees C in a rotary furnace. The 168 h leaching test on filter residue, representing the fraction that may escape the flue gas treatment system, indicated rapid release of Pb and other contaminants. Caracolite and KCl x 2PbCl2 are significantly dissolved, and anglesite and cotunnite form the alteration products, as was confirmed by mineralogical analysis and PHREEQC-2 modeling. The observed Pb-bearing chlorides have significantly higher solubility than anglesite and, following emission from the smelter stack, can readily dissolve, transferring Pb into the environmental milieu (soils, water, inhabited areas).
Keywords: Air Pollutants; Microscopy, Electron, Transmission; mikroanalýza elektronovou sondou; Lead; Česká republika; Industry; látky znečišťující vzduch; olovo; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Electron Probe Microanalysis; transmisní elektronová mikroskopie; průmysl; Czech Republic